Modernización del sistema automatizado para el proceso de pasteurización de crema en la Cooperativa de Productores de Leche, Dos Pinos R.L - Vargas-Arce, Ricardo Antonio (Instituto Tecnológico de Costa Rica, 2019)
The “Cooperativa de Productores de leche Dos Pinos R.L” has 9 pasteurizing plants, with which the proper heat treatment is given to the different dairy products produced by the company. In this case the plant number 3 (P3) is the one used for the production of cream, this is one of the most important because a large number of products involves the use of cream. For reasons of continuous improvement that the company has, an investigation has been carried out, resulting in the pasteurization system of the P3 must be modernizw, since it has been working continuously for 20 years, so its operation has been losing strength, In addition to this, the controller that performs the automation of the process was declared obsolete the previous year, losing any type of maintenance or updating by its founding company (Allen-Bradley). With a new pasteurization system the cooperative expects that the constant processing of cream increases, because the robustness of the pasteurizing plant will be greater and thus failures are avoided, which stop the processing of the product, thus achieving, producing a greater quantity at a lower time, that in the end will become an increase in the overall production of the cooperative. This report presents the way in which the design for the modernization of the pasteurization system was carried out. The main changes to be made are shown, determining that the investment to be made in new equipment is $18.179. The operation of the design was checked based on software simulation, considering the Pinning Chart that the complete pasteurization process entails.
Proyecto de Graduación (Licenciatura Ingeniería en Electrónica) Instituto Tecnológico de Costa Rica. Escuela de Ingeniería Electrónica, 2019.
Keywords: Pasteurización de la leche; Producción agropecuaria; Lácteos; Automatización de procesos; Gestión de calidad